Multidimensionality And Renegotiation : Evidence From Transport-Sector Public-Private-Partnership Transactions In Latin America - Estache, Antonio 1957- (The World Bank, 2008)
Multidimensional auctions are a natural and practical solution when auctioneers pursue more than one objective in their public-private-partnership transactions. However, it is difficult to achieve auction efficiency with multiple award criteria. Using auction data from road and railway concessions in Latin America, the probability of renegotiation this paper estimates by a two-stage least squares technique with a binary selection in the first-stage regression. The findings show that auctioneers tend to adopt the multidimensional format when the need for social considerations, such as alleviation of unemployment, is high. This implies that such political considerations could hinder efficiency and transparency in auctions. The analysis also shows that the renegotiation risk in infrastructure concessions increases when multidimensional auctions are used. Rather, good governance, particularly anti-corruption policies, can mitigate the renegotiation problem